Concentração sérica de sulfato de magnésio em gestantes com pré-eclâmpsia, submetidas aos esquemas de Zuspan e de Sibai - Batista, Fernanda Régnier Gaiotto [UNESP] (2015)
Objectives: To compare magnesium sulphate levels in pregnant women diagnosed with imminent eclampsia or eclampsia and the amount of women who reached therapeutic levels when receiving intravenous magnesium sulphate regimens proposed by Zuspan and Sibai. Subjects and Methods: A prospective quasi-randomized clinical trial was conducted, which included 38 hypertensive pregnant women receiving clinical care in a university center for treatment of impending eclampsia or eclampsia. Patients were stratified according to the magnesium sulfate regimen that they were receiving in: Zuspan regimen group (20 patients) and Sibai regimen group (18 patients). Serum magnesium levels were measured at 9 time points: prior to treatment, 15', 30', 60 ', 90', 2 hours, 4 hours, 12 hours and 24 hours after treatment. For all analyzes, a significance level of 95% (p <0.05) was used. Results: The mean serum magnesium level at the Sibai regimen group was significantly higher when compared to the Zuspan regimen group at all times listed. Only in the Sibai regimen group, the mean serum level reached magnesium therapeutic values, however only in three time points (15 ', 12 hours and 24 hours). In the Sibai regimen group, a greater number of women reached the therapeutic magnesium sulfate level, which was significant the 30 minutes, 60 minutes, 2 hours, 4 hours and 12 hours dosages when compared to the Zuspan regimen group. Conclusion: Sibai regimen group maintained a higher serum level of magnesium when compared to the Zuspan regimen group and a greater number of women who have reached therapeutic levels of magnesium sulphate considered in the literature